REPRESENTASI SEJARAH DALAM MANGA SHANAOU YOSHITSUNE KARYA SAWADA HIROFUMI - Dianti Putri, I Gusti Agung Ayu Made (Humanis, 2016)
Shanaou Yoshitsune is one of comics that use history as setting in literature work and its called historical fiction. The comic representated the life of a great Japanese figure, Minamoto no Yoshitsune. According to the result of analysis, there are historical events and fictional events in the comic. The historical events which representated in Shanaou Yoshitsune comic are ushiwakamaru’s isolation, naming of Shanaou, Yoritomo’s isolation, and Shanaou headed for Hiraizumi. The fictional events in comic are divided into three parts. They are functional event, link event, and reference event. The part of functional events in the comic are the meeting between Ushiwaka and Hyota, the death of Ushiwakamaru and the meeting between Shanaou and Musashibo Benkei. Kurama temple’s test and the meeting of Shanaou and Oniwakamaru are part of link event and the part of reference events are fire in Kurama temple and  Benkei’s romance story. The author is using historical event as background story and input his ideology and then fiction added to make the story more interesting and attractive.
Keywords: historical representative, new historicism, Yoshitsune